Automatic handwash / Mohammad Luqman Ismail, Nur Shahirah Zulkarunain and Nurulasyikin Rosli - Ismail, Mohammad Luqman; Zulkarunain, Nur Shahirah; Rosli, Nurulasyikin (2015)
This project is about to create an automatic hand wash system. This automatic hand wash system is more advanced than the conventional hand wash and it is designed for improved life by having more convenient system. For instance, the water, soap and dryer integrate all into the system. The system is using the light dependent resistor which is its function when it does not detect light. If the sensor detects the light, the operation will not function. For the circuit, water, soap and dryer are controlled by using PIC 16F877A and the voltage source use are 12V. For the output, this circuit is using a pump to flow out the soap and control the water flow